Transformational Leadership, Organizational Culture and Organizational Commitment in Forming Performance in Secretariat Employees DPRD Surakarta - Tahapary, Yuneth; Rahadhini, Marjam Desma; Suprayitno, Suprayitno (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2018)
Abstract : Human resource management is one of the functions of the organization, and when the function is running well, the organization is expected to strive for employees to provide optimal performance in accordance with the expected. Factors that may affect employee performance are transformational leadership, organizational culture and organizational commitment. Transformational leadership is a state in which employees feel trust, admiration, loyalty, and respect for their leaders. Organizational culture is the norm, belief, attitude and philosophy that embraced someone in achieving organizational goals. Organizational commitment is a psychological state that characterizes the relationship of employees with the organization and that affects employees will remain in the organization or not. The object of this research is Secretariat Staff of DPRD Surakarta. Based on presurvey in Secretariat DPRD Surakarta has a phenomenon of human resources problems, namely: the leader can not be a good example for employees, there are leaders who often come late, not obey the rules set. Employees have difficulty completing tasks on time, so the job becomes ineffective. Employees are also less confident about the organization, because of the lack of rewards for employees who have good performance.Abstraksi : Manajemen sumber daya manusia adalah salah satu fungsi organisasi, dan ketika fungsinya berjalan dengan baik, organisasi diharapkan berusaha agar karyawan dapat memberikan kinerja yang optimal sesuai dengan yang diharapkan. Faktor-faktor yang dapat mempengaruhi kinerja karyawan adalah kepemimpinan transformasional, budaya organisasi dan komitmen organisasi. Kepemimpinan transformasional adalah keadaan di mana karyawan merasa percaya, mengagumi, kesetiaan, dan menghormati pemimpin mereka. Budaya organisasi adalah norma, keyakinan, sikap dan filosofi yang merangkul seseorang dalam mencapai tujuan organisasi. Komitmen organisasi adalah keadaan psikologis yang mencirikan hubungan karyawan dan organisasi yang mempengaruhi karyawan akan tetap berada di organisasi atau tidak. Objek penelitian ini adalah Staf Sekretariat DPRD Surakarta. Berdasarkan presurvey di Sekretariat DPRD Kota Surakarta, ada sejumlah masalah sumber daya manusia, yaitu: pemimpin yang tidak memiliki contoh yang baik untuk karyawan, ada pemimpin yang sering datang terlambat, tidak mematuhi aturan yang ditetapkan. Karyawan mengalami kesulitan menyelesaikan tugas tepat waktu, sehingga pekerjaan menjadi tidak efektif. Karyawan juga kurang yakin tentang organisasi, karena kurangnya penghargaan untuk karyawan yang memiliki kinerja yang baik.